(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study was performed to examine the effect of 5-bromo-3-(3-hydroxyprop-1-ynyl)-2H-pyran-2-one (BHP) on the rate of cell proliferation and apoptosis induction in the PC3, human prostate carcinoma cell line. The cell viability was assayed by using sulphorhodamine B staining and apoptosis by annexin V and flow cytometry analyses. The results revealed that BHP treatment in PC3 cells caused a significant reduction in the rate of cell proliferation in dose- and time-dependent manner. Compared to the un-treated cells, the formation of HUVEC tubes was markedly inhibited on treatment with BHP at a concentration of 30 µM. Further investigation revealed the expression of HMGB1, IL-6 and IL-8, pro-inflammatory cytokines was also inhibited on treatment with BHP. Therefore, BHP treatment plays an important role in inducing apoptosis in the prostrate cells and can be of therapeutic value for the prostate cancer treatment.